Analisis Putusan (Award) Arbitrase Internasional ICSID Dalam Churchill Mining Cases Versus Pemerintah Indonesia - Fidelia Fidelia; Syahmin AK (Universitas Sriwijaya, 2018)
ICSID Arbitration as an institution under World Bank is an institution as a dispute settlement, special for handling in the field of investment. As a dispute resolution Institution, ICSID Arbitration has its own mechanism on finishing a dispute which filed, where the steps and mechanism were different with other arbitration Institution. Therefore, there were some question about how this mechanism done well by this ICSID Arbitration in finishing investment dispute. This research used normatif research method which has qualitative to search a implementation based on ICSID Convention, Regulation and Rules of Procedure, the United Kingdom- Indonesia Bilateral Investment Treaty and Republic of Indonesia National Law included. From this research could be known that this investment consisted of some steps, they were file request, screening of a request and registration, number of arbitrators and method of appointment, selection and appointment of Tribunal members, constitution of the Tribunal, first session, other procedures (for Churchill Case only provisional measures used), written procedure, evidence, oral procedure, deliberations, until publication of award.